The ARRIVE Trial: Towards a universal recommendation of induction of labour at 39 weeks?. (January 2020) - Migliorelli, Federico; De Oliveira, Sara S.; Martínez de Tejada, Begoña
Abstract: Both caesarean surgery and induction of labour are common practices performed in all labour wards in an attempt to reduce adverse obstetrical and neonatal outcomes. Recent evidence, notably from the ARRIVE Trial, demonstrated that elective induction at 39 weeks reduced the rate of caesarean deliveries and pregnancy-related hypertensive disorders. However, some concerns have to be addressed as the benefits of universal policies have to be weighed against the actual circumstances of their implementation, the economic impact, the number of procedures needed in order to effectively reduce complications and, above all, women's perception towards this approach at the end of pregnancy. Further research is needed to explore individual tailored strategies in order to offer a personalized prognosis to each woman, rather than a blanket application of general recommendations.